2016
DOI: 10.1002/ece3.1910
|View full text |Cite|
|
Sign up to set email alerts
|

Old males reduce melanin‐pigmented traits and increase reproductive outcome under worse environmental conditions in common kestrels

Abstract: Secondary sexual traits displayed by males and females may have evolved as a signal of individual quality. However, both individual quality and investment on producing or maintaining enhanced sexual traits change as individuals age. At the same time, the costs associated to produce sexual traits might be attenuated or increased if environmental conditions are benign or worse respectively. Accordingly, environmental conditions are expected to shape the association between the expression of sexual traits and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 73 publications
(160 reference statements)
2
10
0
Order By: Relevance
“…Furthermore, those males marked when young and recaptured as mature, indicated that spot size diminished with age, a result in agreement with previous findings in other wing-pigmented damselflies (Mnais: Sanmartín-Villar, 2017; Polythore: Sanmartín-Villar & Cordero-Rivera, 2016). Whether these changes are adaptive, as apparently occurs with changes in coloration with age in other taxa (Dreiss & Roulin, 2010;Lopez-Idiaquez et al, 2016) remains to be studied. It seems, therefore, that black wing spots in P. zoe are important for agonistic interactions, and that over their life, males lose part of their signals of quality.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, those males marked when young and recaptured as mature, indicated that spot size diminished with age, a result in agreement with previous findings in other wing-pigmented damselflies (Mnais: Sanmartín-Villar, 2017; Polythore: Sanmartín-Villar & Cordero-Rivera, 2016). Whether these changes are adaptive, as apparently occurs with changes in coloration with age in other taxa (Dreiss & Roulin, 2010;Lopez-Idiaquez et al, 2016) remains to be studied. It seems, therefore, that black wing spots in P. zoe are important for agonistic interactions, and that over their life, males lose part of their signals of quality.…”
Section: Discussionsupporting
confidence: 88%
“…Laying date (LD t+1 ) was also included in all models to control for the differences in reproductive performance across the breeding season. Previous studies in this species have shown that clutch size is positively associated with age in males [ 51 ]. To control for the potential effects of this variable we included minimum age as an explanatory variable.…”
Section: Methodsmentioning
confidence: 99%
“…, López‐Idiáquez et al . ). The idea that a directional female preference for more ornamented males promotes directional selection in male ornaments might explain a greater detachment of plumage coloration from other traits in male Common Kestrels, resulting in a weak phenotypic integration (Pigliucci & Preston ).…”
Section: Discussionmentioning
confidence: 97%